2014
DOI: 10.1177/1071100714558510
|View full text |Cite
|
Sign up to set email alerts
|

Technical Tip and Cost Analysis for Lesser Toe Plantar Plate Repair With a Curved Suture Needle

Abstract: Level of Evidence:Level V, expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Some studies have proposed using suture passing techniques for plantar plate repairs [ 29 , 47 49 ]. Clement et al reported a technical tip of direct plantar plate repairs using a single skin hook to distract the distal end of the plantar plate and passing sutures with small-radius curved needles [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have proposed using suture passing techniques for plantar plate repairs [ 29 , 47 49 ]. Clement et al reported a technical tip of direct plantar plate repairs using a single skin hook to distract the distal end of the plantar plate and passing sutures with small-radius curved needles [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have proposed using suture passing techniques for plantar plate repairs [ 29 , 47 49 ]. Clement et al reported a technical tip of direct plantar plate repairs using a single skin hook to distract the distal end of the plantar plate and passing sutures with small-radius curved needles [ 29 ]. Clements and Ghai reported the case of a plantar plate injury that was treated using Keith needles to pass sutures through the plantar plate and a bent angiocatheter needle as a hook to retrieve the suture [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, further technique modifications may allow for this technique to be applied to an arthroscopic approach to plantar plate repair. This technique may also reduce cost as compared with industry-designed plantar plate repair systems 16…”
Section: Discussionmentioning
confidence: 99%
“…This technique may also reduce cost as compared with industry-designed plantar plate repair systems. 16…”
Section: Discussionmentioning
confidence: 99%